Synchrotron-limited particle acceleration in relativistic shearing flows - Rieger, Frank M.; Duffy, Peter (The astrophysical journal, 2025)
Fermi-type shear particle acceleration is a promising mechanism for sustaining ultrarelativistic particles along the kiloparsec scale jets in active galactic nuclei. We explore the possibility of synchrotron-limited electron acceleration in mildly relativistic shearing flows and present numerical solutions to the corresponding particle transport equation. We compare our findings with analytical calculations to infer an effective electron cutoff energy, and discuss the relationship to a simplified box model treatment. The results show that mildly relativistic large-scale jets offer a suitable environment for distributed electron acceleration beyond Lorentz factors of γe ∼ 108.
Gesehen am 08.12.2025